The Role of AI in Developing Academic Writing Competence: A Cross-Institutional Analysis of Higher Education - Khabib Muafi; Vivi Amanda; Yessi Darmayanti; Uchy Mukho Adrianty; Rianto Rianto; Solehatur Rizkiyah (English Education and Literature Journal (E-Jou), 2026)
This study investigates the role of artificial intelligence (AI) in developing academic writing competence among English education students in higher education. Employing a comparative mixed-methods design, the research involved first-semester students from UIN Bukittinggi and Universitas Rokania during the 2025–2026 academic year. Data were collected through pre- and post-writing tests, a Technology Acceptance Model (TAM)-based survey, and semi-structured interviews. Quantitative findings reveal significant improvements in students’ academic writing performance in both institutions, with an average score increase of 12.2 points at UIN Bukittinggi and 7.9 points at Universitas Rokania. Improvements were evident in grammatical accuracy, argumentative coherence, and citation accuracy. Qualitative results indicate that students who received structured AI literacy training engaged more critically with AI feedback, while students without institutional guidance tended to rely passively on AI output. The findings demonstrate that AI-assisted writing is most effective when supported by institutional policies, pedagogical scaffolding, and ethical guidance. This study contributes to the growing discourse on responsible AI integration in academic writing instruction in higher education